1997
DOI: 10.1541/ieejpes1990.117.7_930
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a Large-capacity and Long-distance Transmission System by an Adjustable Speed Flywheel Generator

Abstract: SUMMARYAn adjustable-speed flywheel generator (FWG) can control both active power and reactive power rapidly. We have studied the effect of FWG installation on a largecapacity, long-distance transmission system, especially when the system includes loops. In this paper, we describe the selection of FWG location, the selection of stabilizing control input signal, and the required quantities of FWG. FWG location is selected by a PQ-sensitivity method, calculation of which is simple and permits easy understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…A control algorithm has already been proposed for this purpose [3]; specifically, ∆ω of the generator (synchronous machine) or ∆f at the FWG location is used as the input signal.…”
Section: Adjustable Speed Fwg [3]mentioning
confidence: 99%
See 4 more Smart Citations
“…A control algorithm has already been proposed for this purpose [3]; specifically, ∆ω of the generator (synchronous machine) or ∆f at the FWG location is used as the input signal.…”
Section: Adjustable Speed Fwg [3]mentioning
confidence: 99%
“…Points F, G, K were selected for FWG installation, using the PQ sensitivity method [3,8]. The authors have shown in a previous study [3] that when system stabilization is performed by absorption of active power with an adjustable speed FWG, stabilizing control is required in order to keep the slip of the FWG rotor within a certain range, which can be implemented by using ∆ω or ∆f as the input signal.…”
Section: Stabilization Effect Of Adjustable Speed Fwg Used Separatelymentioning
confidence: 99%
See 3 more Smart Citations